Arylethynyl‐Substituted Tristriazolotriazines: Synthesis, Optical Properties, and Thermotropic Behavior1. Issue 15 (10th April 2014) - Glang, Stefan; Rieth, Thorsten; Borchmann, Dorothee; Fortunati, Ilaria; Signorini, Raffaella; Detert, Heiner
Abstract: The synthesis of C 3 ‐symmetrical tristriazolotriazines with conjugated arms and lateral alkoxy side chains was performed by a threefold condensation of cyanuric chloride with tetrazoles. Conjugated π segments include phenyl, tolane, and its phenylethynyl‐elongated homologue. Disclike and a dendritic molecule have been obtained, and two compounds with a 3, 4, 5‐tris(octyloxy) substitution form broad thermotropic mesophases. The linear optical properties, solvatochromism of the fluorescence, acidochromism, and the two‐photon absorption efficiency of selected compounds are reported. Abstract : Star‐shaped and dendritic molecules with a triphenyl‐tristriazolotriazine core and flexible side chains are prepared from tetrazoles and cyanuric chloride. The optical, nonlinear optical, and thermotropic properties of these compounds as well as their phenylethynyl homologues are reported.